Surveillance experiences of extinction rebellion activists and police: Unpacking the technologization of Dutch protest policing - Majsa Storbeck; Gabriele Jacobs; Marc Schuilenburg; Robin van den Akker (Big Data & Society)
Recent years have witnessed an intensifying debate on the deployment of emerging surveillance technologies in protests. Often discussed in terms of “chilling effects”—where activists self-censor due to fear of surveillance repercussions—there's limited research on its effects on both activists and law enforcement. This study explores the technologization of protest policing, moving beyond the oversimplified cat-and-mouse game analogy, to examine its effects on surveillance experiences in more nuanced ways. By analyzing observations and interview data from 2023 road blockades by Extinction Rebellion in The Hague, Netherlands, this paper highlights the intricate consequences of surveillance technologies for both sides. Moving beyond the narrow legal interpretation of “chilling effects,” it uncovers two further socio-psychological sub-manifestations, showing how both groups adapt through hyper-transparency (extreme openness) and hyper-alertness (extreme caution). The study demonstrates how these experiences can be self-reinforcing, where reciprocal suspicion might contribute to a cycle of mutual distrust beyond protest contexts, but also introduces new forms of resilience. This cycle, despite lacking clear causality, bears important implications for society at large. Pervasive suspicion erodes institutional trust among activists and threatens the traditionally communicative and de-escalation-focused approach of Dutch law enforcement. Overall, this extended impact indicates that the technologization of protest policing has resulted in a hybridization of screens and streets, causing its human impacts to stretch beyond the specific times and places of demonstrations. Protest policing now encompasses a multifaceted spectrum of surveillance experiences, affecting a plethora of public values, beyond the right to protest alone.